PELATIHAN PENGGUNAAN MOBILE MARKETPLACE PADA KELOMPOK TANI SAYUR DESA TORONG REJO BATU - Irawan, Dwi; Affan, Muhammad Wildan (Universitas Muhammadiyah Malang, 2021)
The Vegetable Farmer Group is one of the active groups in Batu City, namely in Torong Rejo Village. The economic situation affected by the existence of ccovid 19 also had an impact on the sale of agricultural products from Gapoktan. To minimize the spread of Covid 19, the mobile marketplace is an alternative to get around the prohibition of meeting directly between sellers and buyers to reduce the spread of Covid-19 while still encouraging economic movement, especially the sale of Gapoktan farmers. This method of dedication is carried out by discussing and demonstrating the use of the mobile marketplace. The result is that vegetable farmer groups have begun to be able to use the mobile marketplace, both for selling the products they produce to buying agricultural necessities. By using the mobile marketplace, it is hoped that it can minimize the vegetable supply chain from farmers to consumers, so that it can increase profits on sales because farmers can directly sell to end users.